Os pobres no evangelho segundo Lucas: um estudo da terminologia para expressar o mundo dos pobres no evangelho segundo Lucas e no antigo testamento, uma realidade que interpela ainda hoje. - Souza, Ana Lúcia Alencar de (2023)
The present research intends to resume and rethink a reality of all times, the existence of poverty, from the testimony of the ancients, present in the biblical texts. Throughout Scripture, the notion of poverty is mentioned, and the poor are presented as those who are preferred by YHWH, precisely because they are abandoned and exploited by the ruling class. In this work, some aspects and nuances of the terminology related to the poor/poor will be seen; however, emphasis will be placed on economic and social poverty. For a better understanding, the study of the terminology for the poor/poor in the Old Testament literature in relation to the terminology in the Gospel according to Luke is the material object that will guide this research. Therefore, the research will aim to research the vocabulary related to the theme of the poor in the Gospel according to Luke, putting it in relation with the terminology used in the Old Testament for this theme, considering the interpellations of this reality for the current world. The research will be developed from bibliographical investigation of comments; biblical and theological dictionaries, as well as Greek-Portuguese and Hebrew-Portuguese dictionaries, as well as research in magazines, periodicals, digital and printed articles, with a hermeneutic focus within a political, social and pastoral perspective. The research will be presented in three stages: the first will expose the terminology related to poor/poverty in the Old Testament literature; then, and having the Gospel according to Luke as a source, a historical-literary analysis of the lucan text will be made, and, for a greater understanding of the reception and application of the terminology referring to poor/poverty in the message of the good news of Jesus to his community ; for that, the following passages will be analyzed: Lk 1,46-56; 4.14-30; 16.19-31; 21.1-4. The third stage deals with the response of Christians today to the good news for the poor, coming from the Old Testament and endorsed by Jesus Christ. Among the many challenges and scourges that plague postmodern humanity is the scandal of poverty, demanding from the Christian community a renewal of commitment to the good news of Jesus that was primarily for the poor and suffering. The message of the Gospel of Christ refutes aporophobia and emphasizes charity and empathy towards the subject of poverty.